Barcoding non-indigenous macroalgae in the Azores - Santos, Rodolfo (2016)
ABSTRACT: Algae invasions in marine habitats represent a recognized worldwide threat to the integrity of native communities, to economy and even to human health. The em phasis of the present work is on non-indigenous marine macroalgae species in the Azores.